P857 Penile microbiome and urinary cytokines of kenyan men who have sex with men and men who have sex with women. (14th July 2019) - Mehta, Supriya; Nandi, Debarghya; Okal, Duncan; N'Gety, George; Green, Stefan; Otieno, Fredrick; Obondi, Eve; Kinslow, Jennifer; Bhaumik, Dulal; Bailey, Robert; Landay, Alan
Abstract : Background: MSM are disproportionately affected by HIV and STIs compared to men who have sex with women (MSWomen). This may be due in part to different burden of mucosal inflammation. We compared penile microbial composition between MSM and MSWomen and association with mucosal inflammation. Methods: In this cross-sectional study, we enrolled 43 MSM and 43 MSWomen, who were HIV negative and matched on age and circumcision status. The penile microbiome was assessed via meatal swab, with 16S rRNA gene amplicon sequencing. Urinary cytokine concentrations (TNF-α/IL-1β/IL-8/IL-10/IP-10) were measured using Luminex. Random Forest (RF) identified genus-level taxa differing between MSM and MSWomen. Taxa from RF were regressed on cytokine outcomes, with multiple testing correction and information criterion model selection. Results: Men were median age 24 and 77% circumcised. There were substantial differences in educational attainment, employment, alcohol and drug use, condom use, and number of sexual partners, with MSM having greater behavioral risks. Microbiome composition differed markedly between MSM and MSWomen: RF discriminated between MSM and MSWomen with 84% accuracy. Taxa with greatest discriminating influence were Lactobacillus, Anaerococcus, and Staphylococcus . In crude analysis, cytokines TNF-α/IP-10/IL-10 were elevated among MSWomen (p<0.05, each); IL-8 did not differ by group; IL-1β was higher among MSM (p=0.03). Cytokine concentration increased in response to Corynebacterium (IL-8/TNF-α/IP-10/IL-1β), Gardnerella (IL-8/IP-10/IL-1β), Veillonella (IL-8/IP-10/IL-1β), and Peptoniphilus (IL-8/IL-1β). Microbiome composition did not account for the difference in TNF-α, IP-10, or IL-10 between groups; the difference in IL-1β became non-significant after accounting for taxa. Among MSWomen, IL-1β (p=0.01) and IL-8 (p=0.05) were elevated if the female partner had BV. Conclusion: To our knowledge, this is the first comparison between MSM and MSWomen of penile microbiome and urinary cytokines. Future studies should examine whether microbiome and mucosal inflammation differences between MSM and MSWomen cause differential risk of HIV/STI acquisition or differential impact on efficacy of HIV/STI interventions. Disclosure: No significant relationships.